Vibration impact towards deformable laterite soil with different moisture content - Abd. Rashid, M. F. (2019)
In engineering practice, natural and man-made vibration phenomenon can cause dynamic stress to be imposed on soils such as blasting, construction operations and machinery, and vehicle traffic vibrations. This issue need to be addressed to ensure the geo-environment is sustainably secure. Laboratory experiments were conducted to characterize the behaviour of vibrated deformable double-porosity under different moisture content in repeated vibration. This paper presents the investigation of vibrated double-porosity soil by aggregating laterite soil with 29%, 32% and 34% moisture content. The experiments were conducted by using acrylic soil column, accelerometer and vibrating table. Aggregated laterite soil is poured in acrylic soil column then compress until 10 cm height. High-frequency accelerometers were installed to observe acceleration at 2 points; (1) surface of soil sample, and (2) surface of vibrating table. The experiments for repeated vibration were conducted by increasing the amplitude of the vibrating table. The acceleration time histories at accelerometers were collected to observe maximum amplitude. The results showed that the acceleration response in non repeated vibration was increased with increasing of moisture contents. It was found that with vibrated samples, the soil structure was rearrange and porosity characteristics identified as expected influence the speed of liquid penetration.